Law librarianship in academic libraries : best practices - Dina, Yemisi (Chandos information professional series., 2015)
In the last two decades, advancement in technology has transformed every aspect of librarianship. Law Librarianship in Academic Law Libraries discusses issues and model practices in academic law libraries. This text will help librarians and library school students understand the operation, resources and facilities that are available in the academic law library. It explains the practices and trends that are widely practiced in different parts of the world. This book describes the expectations of an aspiring professional with an interest in specializing in law librarianship; revealing facts pertaining to management and administration which are not necessarily taught in library schools. The first chapter introduces the history of academic law libraries, and defines law librarianship. The remaining chapters are dedicated to different aspects of law librarianship including the importance of emerging technologies and how they are implemented in the academic law libraries setting, finishing with a concluding chapter on global opportunities available for law librarians.